Scaffolded reaching can encourage motor development: Commentary on van den Berg & gredebäck (2020). Issue 4 (15th February 2021) - Libertus, Klaus
Abstract : Recent findings regarding the effectiveness of sticky mittens training as a motor intervention have been mixed. This commentary argues that despite inconsistent results, overall patterns suggest that sticky mittens may facilitate reaching behavior. More research on this topic is needed.